Bilateral agreement for academic years 2007/2010 LLP (Lifelong Learning Programme) - Erasmus between Universidade Lusíada de Lisboa and Université Nancy - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the Lifelong Learning Programme. - Erasmus subject area – Psychology and behavioural sciences.